In the shadow of the cape: Superman and disruptivity - Tembo, Kwasu David (The University of Edinburgh, 2016)
The discourse regarding contemporary comic book studies has become increasingly concerned with the apocalyptic potential of the power of comic book superbeings. While many consider Superman to be a morally upright and hopeful figure worth emulating, the idea of a creature as powerful and uncannily similar to human beings as Superman is produces a type of paranoia, distrust, and unease. This type of disruptivity is a result of the combination of two foundational aspects of the character's being namely, its power, and its uncanny Otherness. Recent trends in the discourse concerning the cinematic depictions of the unavoidably destructive aspects of Superman's power indicate that the disruptive aspects of the character's being cannot be ameliorated by conventional appeals to dialectical arrangements of moral categories including good and evil. This also applies to nostalgic interpretations of the character that seek to dissolve the inextricable connection between the utopian and dystopian potential inherent in its power and Otherness in an idealized history. Situating itself between the aesthetic and historical comic book theory of Thomas Inge, Peter Coogan, Danny Fingeroth, Christopher Knowles, Clive Bloom, and Greg McCue and the philosophies/xenologies and critical approaches of Robert Freitas Jr., Michel Foucault, and Fredric Jameson, this project uses the concepts of the character's power, body, and Otherness to examine the existential and socio-political consequences of Superman's disruptivity on a diegetic earth.
Keywords: Superman; comic books; power; otherness; xenology